(untitled) (Bangladesh Journal of Urology, 2026)
Background: Benign prostatic hyperplasia (BPH) is commonly seen in elderly male. α1 adrenoceptor antagonists is considered to be the first line treatment as pharmacological therapy, such as treatment with tamsulosin, which selectively blocks αla adrenoceptors. As the initial treatment for lower urinary tract problems associated with BPH, al-blockers are generally used. Objective: Aim of the study is to compare the efficacy of tamsulosin and silodosin in the management of symptomatic benign prostatic hyperplasia. Methodology: This quasi-experimental study carried out in the department of Urology, Sir Salimullah Medical College Mitford Hospital, during the period of January to December 2022. Results: Total 40 patients of 50-80 years of age were consequently selected according to inclusion criteria. After completion of baseline clinical evaluation and investigations, participants were divided into two groups, group A and group B. Group A (n=20) was given Tamsulosin 0.4mg daily at bed time for 2 months. Group B (n=20) was given Silodosin 8 mg per day for 2 months. Efficacy was evaluated of each group after 2 month follow up and lastly a comparison was made between them. The parameters monitored were International Prostate Symptoms Score (IPSS) Maximum urine flow rate (Qmax) and Post Voidal Residual Volume (PVR). Both the drugs are effective in relieving symptoms of BPH but Silodosin is superior to Tamsulosin in improvement of total IPSS (p<0.001) and Qmax (p<0.01) PVR (p<0.01) at the end point. Conclusion: Outcome of parameters at follow up after 2 months. Silodosin group showed significant improvement of IPSS (p<0.05) PVR (p<0.001) and Qmax (p<0.001) than Tamsulosin. The incidence of adverse events by administration of Silodosin was less than that by Tamsulosin. Silodosin appears to have more efficacy and safety than Tamsulosin in symptomatic BPH. Bangladesh J. Urol. 2025; 28(2): 93-99